Seabuckthorn polysaccharide combined with astragalus polysaccharide ameliorate alcoholic fatty liver by regulating intestinal flora - Liu, Jiayue; Kong, Lingzhou; Shao, Mengting; Sun, Changhai; Li, Changxu; Wang, Yanyan; Chai, Xue; Wang, Yuliang; Zhang, Yu; Li, Xiaoliang; Zhao, Hong (Frontiers in Endocrinology, 2022)
Background: At present, the incidence of alcoholic fatty liver disease (AFLD) is increasing year by year, and numerous studies have confirmed that liver diseases are closely related to intestinal flora. Seabuckthorn and Astragalus membranaceus, as medicinal and edible homologous traditional Chinese medicine, have good liver protection, and their polysaccharides can regulate the intestinal flora. Here, we studied the effects of HRP, APS and the combination of the two polysaccharides on the intestinal flora of AFLD mice, aiming to provide a scientific basis for the two polysaccharides in the treatment of AFLD. Materials and Methods: Thirty Kunming (KM) mice were randomly divided into the control group (Con), the model group (Mod), the HRP treatment group (HRP), the APS treatment group (APS), and HRP+APS treatment group (HRP+APS), with six mice in each group. The AFLD model was constructed by continuous intragastric administration of 42% vol Niulanshan ethanol solution for 28 days, and the mice in each polysaccharide group were given corresponding drugs. The levels of AST, ALT, TC and TG in serum of mice were measured. 16S RNA amplicon sequencing technique was used to determine the diversity and richness of intestinal flora, and the relative abundance level of phylum level and genus level in each group. Results: Compared with the Mod group, HRP, APS and HRP+APS could reduce the serum levels of AST, ALT, TC and TG in mice. In addition, HRP, APS and HRP + APS restored the diversity, relative abundance and community structure of intestinal mucosa bacteria in AFLD mice to a certain extent. Meanwhile, HRP, APS and HRP + APS could reduce the ratio of Firmicutes to Bacteroidetes, and ultimately increase the abundance of beneficial bacteria and reduce the abundance of pathogenic bacteria. Conclusion: HRP, APS, and HRP+APS can improve the intestinal microecology of AFLD model mice, alleviate liver injury, and maintain normal intestinal function in different degrees.